Georgia : Request for a Stand-By Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Georgia. (IMF Staff Country Reports; Country Report, 2022)
The authorities' policy response aided a robust recovery from the COVID-19 shock in 2021 with output growth above expectations reflecting pent-up demand and strong export performance. However, spillovers from the war in Ukraine are expected to dampen growth, raise inflation, and widen the current account deficit this year. The recovery in 2021 and scaling back of pandemic measures led to a decline in the fiscal deficit and government debt. Inflation is expected to remain higher for longer, reflecting elevated global food and commodity prices. The NBG has increased its policy rate by 3 percentage points since March 2021.